Lietuvių kalbos gauti ir tekti: gramatinimo aspektai - Jasionytė, Erika (Baltistica, 2009)
LITHUANIAN gauti (‘GET’) AND tekti (‘BE GOTTEN’): ASPECTS OF GRAMMATICALIZATIONThe paper deals with the Lithuanian get-verbs gauti (‘get’) and tekti (‘be gotten’) within the framework of grammaticalization. The purpose of the paper is to analyze semantic as well as morphosyntactic properties of the verbs under the study and to disclose their tendencies towards grammaticalization. Following the point of view that the very beginning of the process of grammaticalization is in the context of a particular construction the focus of the paper is on the constructional patterns in which the verbs gauti (‘get’) and tekti (‘be gotten’) appear and on the basic types of complements of the verbs. Since frequency is considered to be an important indicator of grammaticalization, the paper looks at the quantitative distribution of basic structural types of complements used with the Lithuanian get-verbs under analysis. Besides, types of modal meanings which gauti (‘get’) and tekti (‘be gotten’) denote are analyzed as well.The Lithuanian verbs gauti (‘get’) and tekti (‘be gotten’) express an ingressive aspect of possession, i.e. onset of possession or acquisition. As lexical verbs with the meaning of acquisition the Lithuanian get-verbs are found in the constructional patterns with NP as their grammatical object. When the noun possessed denotes a concrete entity, the verbs have the meaning of concrete acquisition, and when the noun denotes an abstract entity, the verbs express an abstract acquisition. Both verbs gauti (‘get’) and tekti (‘be gotten’) more often tend to express abstract acquisition. However, there are some differences in the possibilities of expressing the lexical meaning of acquisition: only the verb gauti (‘get’) most frequently functions as the full lexical verb and the verb tekti (‘be gotten’), in contrast, functions as the modal verb.Modal meanings of the Lithuanian get-verbs are expressed by the constructions with an infinitival complement (INF). Both of the verbs gauti (‘get’) and tekti (‘be gotten’) denote non-epistemic necessity and non-epistemic possibility. However, the meaning of non-epistemic possibility seems to be very peripheral for the Lithuanian get-verbs. It is worth to notice that the modal verb tekti (‘be gotten’), besides its modal meanings, in certain contexts tend to mark aspectual meaning of perfectivity. However, the conclusion about the status of the verb tekti (‘be gotten’) as an aspectual marker requires further analysis.
Keywords: lietuvių kalba; veiksmažodis